Mengukur Akuntabilitas Kinerja Sekretariat Daerah Kota Mataram - Rifaid, Rifaid; Wahyu, Nomi; Jafar, M. Ulfatul Akbar (JIAP (Jurnal Ilmu Administrasi Publik), 2022)
This article discusses the performance accountability of the Mataram City Regional Secretariat. A good performance report will have an impact on the quality of good governance. The method used is qualitative with a descriptive approach, data collection techniques using interviews, observation and documentation. The results of the study show that the accountability of the performance of the Regional Secretariat of the city of Mataram is quite good, both in measuring the performance of activities and target performance. However, the improvement in the quality of program or activity implementation through increased budget coordination, the quality of human resources in order to achieve usability and usability is still not optimal.